Transverse-Direction Post-Seismic Running Safety of Longitudinally Connected Ballastless Track–Continuous Girder Bridge Systems Considering Earthquake Damage State - Yulin Feng; Shenglin Xu; Bitao Wu; Wangbao Zhou; Xiang Liu; Liangqin Wu; Junhuan Rao; Ping Xiang; Zhongzhao Guo (Buildings, 2024)
The transverse-direction post-seismic running safety of a longitudinally connected ballastless track-continuous girder bridge (LCBTCGB) system considering earthquake damage state (EDS) was studied. In this study, a simulation model of an LCBTCGB was established, and the post-earthquake damage law of the LCBTCGB was analyzed by selecting the ground motion that had the greatest influence from within the existing studies. The EDS of key interlayer components and the residual deformation law of each layer structure of the LCBTCGB system were defined. Subsequently, the residual deformations and EDS from the simulation model were imported into a coupled dynamic model of the train, track, and bridge. Evaluation of running safety evaluation after an earthquake was carried out with and without considering EDS, and a running safety guidance diagram for after an earthquake is provided. The results revealed that under conditions of rare earthquakes, without considering EDS, the running safety judgment after the earthquake were underestimated, and the risk increased by 13.6%. Following the designed earthquake, the running safety risk after the earthquake increased by 18.7% if EDS was not considered. The risk of the running safety index exceeding the limit did not increase linearly with earthquake intensity with and without considering EDS. When the EDS was considered, derailment coefficients and wheel axle lateral forces exceeded the safety limit value at an earthquake intensity of 0.2 g, whereas these limit values were only exceeded at an earthquake intensity of 0.3 g when EDS is ignored. When the earthquake intensity reached 0.5 g, the influence on the derailment coefficient was greater but the difference in the wheel axle lateral forces was not significant with or without considering EDS. It is suggested that EDS should be considered when post-seismic running safety of LCBTCGBs are analyzed; otherwise, it will lead to misjudgment of running safety after an earthquake.